Efektifitas Daya Pembersihan Minyak Kelapa Murni (Virgin Coconut Oil) Terhadap Akumulasi Plak Permukaan Gigi - Sitanaya, Rini; Lesmana, Hans; Irayani, Surya; Septa, Badai; Novitasari (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2023)
Dental plaque is a soft and sticky deposit on the tooth surface consisting of salivary glycoproteins,  extracellular polymers and various bacteria, one of which is Streptococcus mutans. Plaque is a  major factor in the occurrence of various problems in the oral cavity. Plaque formation can be  suppressed by chemical plaque control using mouthwash. Currently, the available mouthwash  contains several chemicals that can cause side effects in the oral cavity, so mouthwashes with  herbal ingredients are starting to be used. Virgin coconut oil (Virgin Coconut Oil) contains 44%-53%  lauric acid is a compound that contains antibacterial which also plays a role in whitening teeth. The  purpose of this study was to determine the effectiveness of gargling with virgin coconut oil (Virgin  Coconut Oil) against plaque accumulation. This type of research is analytic observation. The  method used is one group pre-test post-test design with a cross sectional approach. The research  sample was obtained using a purposive sampling technique, namely the people of Fakkie Village as  many as 32 respondents. The results showed that the average plaque accumulation before rinsing  with virgin coconut oil was 3,484 and after gargling with virgin coconut oil was 2,097. The results of  statistical tests using Paired t test obtained a significance result of 0.000 (p-value <0.05). So it can  be concluded that gargling with virgin coconut oil is effective in reducing plaque accumulation.  Keywords : Gargling; virgin coconut oil; plaque